Evaluation of late blight resistance and agronomic characteristics for B3C1 clones and its segregating progenies under long-day conditions in Korea - Park, K.; Cho, K.; Cho, J.; Chang, D.; Kim, H.; Cho, H.; Landeo, J. (Springer, 2011)
Potato late blight caused by the fungus Phytophthora infestans is the most important disease in the world. Developing potatoes resistant to late blight is a major breeding effort around the world. International Potato Center (CIP) developed a potato population with durable resistance to late blight. These clones (B3C1) were bred in Peru under short-day conditions, growing in long-day conditions such as Korea is not feasible. The purpose of this study was to evaluate late blight resistance and major agronomic characteristics of CIP’s breeding lines, and agronomic potential of segregating progeny from B3C1 under long-day conditions in Korea. Late blight resistance of B3C1 clones was evaluated in naturally infested fields. AUDPC (Area Under Disease Progress Curve) values of all B3C1 clones were significantly lower than those of control varieties Atlantic and Haryeong, indicating B3C1 clones have high levels of resistance. However, most of the B3C1 clones had lower tuber yield compared to control cultivars, presumably due to differences in adaptability to long-day conditions. Two clones, 381580.30 and 392635.54 were susceptible to common scab (Streptomyces scabies) and 384398.56 and 393382.44 had a high percentage of tuber disorders. Four clones, including 391047-34, had relatively high marketable yield, high specific gravity, and desirable agronomic characteristics. To develop clones highly resistant to late blight and with good adaptability in long-day condition, B3C1 clones were crossed with Korean breeding lines. Through individual selection for several years, 25 clones were selected as promising lines with good agronomic characteristics and high resistance to late blight.